Contribution to the structural study of the Rhodiani ophiolites, Vourinos massif - PHOTIADES, A.; ΡΟΜΟΝΙ-ΡΑΡΑΙΟΑΝΝΟΥ, F. (Bulletin of the Geological Society of Greece, 2001)
The Rhodiani area geologically is comprised of a sequence of Mesozoic and Tertiary thrust sheets, including the Jurassic ophiolite and sedimentary covers; they composed of an ultramafic unit overlain by an Albian to Cenomanian redeposited limestone cover, and at the top a volcanic unit that is overlain by neritic to pelagic Upper Jurassic to Upper Cretaceous age limestone and Upper Maastrichtian flysch deposits. These thrust sheets were emplaced over the Pelagonian platform. Therefore the Rhodiani "ophiolite" is not a single thrust unit, but it is an imbricated ophiolite tectonic structure resulting from a two-stage emplacement process; the ultramafic unit was overthrust on the melange of the Pelagonian platform during the initial emplacement (Jurassic) and the volcanic unit was re-thrust on the former during subsequent post-Eocene tectonic phase